Effect of liveweight and body condition on work output from draft oxen - Bartholomew, P.W.; Khibe, T.; Little, D.A. (Springer, 1994)
A trial was carried out to assess the effect of liveweight and body condition on working capacity of Zebu oxen. Over a working period of 9 days, animals which started work with a mean liveweight of 360 kg and body condition score of M+ produced the highest daily work output. At an initial liveweight of 360 kg, body condition had relatively little effect on work output of 3.19 MJ. In contrast, at a mean live-weight of 310 kg. at the start of work, mean daily work output of animals of condition score M+ was significantly lower than that of animals in poorer condition (M-) at 0.81 compared with 2.50 MJ work output per day. It was concluded that body weight as indicated by body size is probably a more useful indicator of likely capacity for work than body condition under the short-season working conditions typical for oxen in the semi-arid zone of central Mali.